Harnessing Educational Media to Cultivate Critical Thinking in STEM Learning Environments - Munawwaroh, Izzatul (International Journal of Instructional Technology, 2024)
This study aims to analyze the role of educational media in improving students' critical thinking skills in a STEM learning environment. Using a qualitative case study approach, this study examines how educational technology can be integrated into STEM teaching to facilitate analytical thinking and problem solving. The subjects of the study included the principal, vice curriculum, teachers and students, at SMAN 1 Paiton Probolinggo. Data collection techniques included classroom observation, in-depth interviews, and documentation analysis. Data were analyzed through the process of data reduction, data presentation, and drawing conclusions. The results showed that high-tech educational media were able to create a more interactive and engaging learning environment, which encouraged students to think critically and solve problems in the STEM context independently. The implementation of interactive media was proven effective in improving students' understanding of STEM concepts, strengthening higher-order thinking skills, and motivating students to be more active in the learning process. On the other hand, teacher competence in using educational media optimally played a key role in achieving the expected learning outcomes. These findings contribute to the STEM education literature and offer new perspectives on how educational media can be utilized to prepare students for real-world challenges through the development of critical thinking skills.